Disparities in the Clinical Encounter: Virginia's African American Children with Special Health Care Needs. (25th September 2011) - Oswald, Donald P.; Bodurtha, Joann N.; Willis, Janet H.; Gilles, Donna L.; Christon, Lillian M.; Ogston, Paula L.; Tlusty, Susan M.
Abstract : This study analyzed Virginia data from the most recent National Survey of Children with Special Health Care Needs. Logistic regression models were run for six Maternal and Child Health Bureau core outcomes and included demographics, child characteristics, health care providers, and health care access variables as predictors. Race/ethnicity disparities were judged to be present if the race/ethnicity variable was a significant predictor in the final model. Examining the components of disparate outcomes, African American children were found to be less likely than their white counterparts to have a usual source for sick and preventive care and to have a personal doctor or nurse. Their parents were less likely to say that doctors spent enough time, listened carefully, were sensitive to values and customs, and made them feel like a partner. These findings emphasize the need to examine health care disparities at a state level in order to guide efforts at remediation.